2020
DOI: 10.3390/cancers12113230
|View full text |Cite
|
Sign up to set email alerts
|

Immune Profiling of Gliomas Reveals a Connection with IDH1/2 Mutations, Tau Function and the Vascular Phenotype

Abstract: Background: Gliomas remain refractory to all attempted treatments, including those using immune checkpoint inhibitors. The characterization of the tumor (immune) microenvironment has been recognized as an important challenge to explain this lack of response and to improve the therapy of glial tumors. Methods: We designed a prospective analysis of the immune cells of gliomas by flow cytometry. Tumors with or without isocitrate dehydrogenase 1/2 (IDH1/2) mutations were included in the study. The genetic profile … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Recently, IDH mutation status has been reported to be associated with PD-L1 expression and tumor-infiltrating lymphocyte (TIL) infiltration in diffuse gliomas. 23 , 24 , 25 , 26 , 27 Our study was largely in agreement with available data but differed in several important aspects. We integrated IDH mutation and 1p/19q codeletion status and conducted a comprehensive and systematic analysis of 28 immune cell types and their infiltration in these subtypes; the expression of the immune checkpoint components in each subtype was assessed and TMB, MSI, and MHC class I gene expression was categorized in these subtypes.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, IDH mutation status has been reported to be associated with PD-L1 expression and tumor-infiltrating lymphocyte (TIL) infiltration in diffuse gliomas. 23 , 24 , 25 , 26 , 27 Our study was largely in agreement with available data but differed in several important aspects. We integrated IDH mutation and 1p/19q codeletion status and conducted a comprehensive and systematic analysis of 28 immune cell types and their infiltration in these subtypes; the expression of the immune checkpoint components in each subtype was assessed and TMB, MSI, and MHC class I gene expression was categorized in these subtypes.…”
Section: Discussionsupporting
confidence: 86%
“…High expression of Targeting Protein for Xenopus kinesin-like protein 2 ( TPX2 ) and Tubulin alpha-1C chain ( TUBA1C ) increases immune cell infiltration in LIHC, LUAD, and LGG, respectively, and is associated with poor prognosis [64] , [65] , [66] . A high level of microtubule-associated protein Tau is inversely correlated with the vascular and immune contents, delaying tumor growth in gliomas [67] . Increased expression of microtubule interacting and trafficking domain containing 1 ( MITD1 ) indicates a poor prognosis with decreased NK cell infiltration in LIHC and increased CD8+ T cells infiltration in KIRC [68] , [69] .…”
Section: Discussionmentioning
confidence: 99%
“…In the LGG cohort, the patients with IDH1 and TP53 mutations seem to have many immunological changes than the patients with wild-type, for example, the anti-viral function (defense response to virus, negative regulation of viral process, and type I interferon signaling pathway), which might indicate that the immune status in the patients with IDH1 and TP53 mutations is different from the patients with wild-type. Previous studies have shown reduced infiltration of immune cells in IDH1 mutant gliomas and suppressed PD-L1 expression, 35 , 36 while TP53 GOF mutation had shown it promotes inflammation and has a profound effect on patient prognosis. 25 In KEGG pathway results, the patients with IDH1 and TP53 mutations suggest more correlation with the other viral infection, such as COVID-19, influenza A, measles, and Epstein-Barr virus, that might be the consequences of the suppression of immune function in these patients.…”
Section: Discussionmentioning
confidence: 95%